A preliminary attempt of direct methanol synthesis from biomass pyrolysis syngas over Cu/ZnO/Al2O3 catalysts - Simanungkalit, Sabar Pangihutan; Jones, Isabelle; Okoye, Chiemeka Onyeka; Zhang, Zhezi; Zhu, Mingming; Zhang, Dongke (Elsevier, 2023)
The possibility of direct methanol synthesis from biomass pyrolysis syngas (BPS) over Cu/ZnO/Al2O3 catalysts was investigated using a fixed bed reactor. A commercial benchmark catalyst and an in-house Cu/ZnO/Al2O3 catalyst prepared using the co-precipitation method, Cu/Zn/Al = 68/28/4 wt%, were tested for methanol synthesis from a model BPS containing 25% H2, 25% CO, 20% CH4, 20% CO2, and 10% N2. The experiments were performed under different conditions of temperature (220–260 °C), pressure (2–4 MPa) and time on-stream (TOS, 0–100 h). Methanol was successfully synthesised with the highest space-time yield of 0.185 g gcat−1 h−1. Higher pressures and lower temperatures favoured methanol production. The fresh and used catalyst samples were also characterised using N2-physisorption (BET), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) to investigate the mechanisms of catalyst deactivation. While CH4 present in the BPS did not affect catalyst performance, the high concentration of CO2 enhanced Cu oxidation, leading to decreased catalyst performance with increasing TOS. After 100 h TOS, the methanol yield obtained over the commercial and in-house catalysts decreased by around 9.2% and 4.3%, respectively. This research has provided new insights into the challenges of producing methanol from unconventional syngas and motivated future work to develop a robust catalyst that can serve syngas with H2-deficient and high concentrations of CO2.
Keywords: Biomass pyrolysis syngas; Catalyst activity; Catalyst deactivation; Methanol synthesis